The Enablers of Student Spin-Offs Intention: A Study in Malaysian Higher Educational Institutions - Abdul Rahman, Zahari; Puteri Fadzline, Muhamad Tamyez; Noor Azlinna, Azizan (GBMR, 2018)
Purpose: This study aims to investigate the enablers (founders’ characteristics, university roles and entrepreneurial environments) of student spin-offs intention. Design/methodology/approach: The data were collected using cluster sampling method. Respondents in eleven Malaysian public universities were approached using an online survey questionnaire. Of these, 369 completed questionnaires were obtained for further analysis. Data was analysed using Partial Least Square-Structural Equation Modelling. Findings: The results show that four of founders’ characteristics such as need for achievement, innovativeness, propensity of risk taking and self-efficacy have positively influence student spinoffs intention. In addition, three constructs like locus of control, university roles and entrepreneurial environments clearly unable to associate with student spin-offs intention. Research limitations/implications: Future studies should include other enablers of student spinoffs intention. Furthermore, longitudinal and qualitative study should also be deployed in the future studies